Microstructure evolution of monocrystalline superalloy with boron addition. (4th October 2019) - Yu, Zhuhuan; Liu, Beilei; Zhai, Xiaowei; Qiang, Junfeng; Mei, Zihan; Fei, Zhenbao
Abstract: The as-cast and heat treated structures of nickel-base monocrystalline superalloy DD90 were observed, using an optical microscope (OM) and a scanning electron microscope (SEM), and the effect of different contents of B on γ / γ ′ eutectic structure, carbide and borides morphology and volume fraction were studied. Boron addition had no significant effect on dendrite morphology, the volume fraction of eutectic increased with the increasing of boron level. The morphology of carbides changed from layers, needle, block and the layer-typed to the smaller block. The morpgologies of carbides in as-cast state mainly were blocky, octahedral and Chinese script like. The carbides precipitated as dispersed blocky and octahedral after thermal treatment. With the increasing of boron level, the volume fraction of borides increased and the content of W + Mo + Cr + Re became much high. The morphology of borides mainly were slender rod and grain after thermal treatment.